Disseminação das tecnologias digitais e promoção da inclusão digital na educação pública: estratégias da governamentalidade eletrônica - Loureiro, Carine Bueira (Universidade do Vale do Rio dos Sinos, 2013)
The aim of this thesis is to discuss the spread of digital technologies (DT) and the promotion of digital inclusion (ID) in education. This questioning was developed from the discursive practices mobilized by four Brazilian programs aimed at spreading the use of TD in public education, put into operation in the period 1980-2010. The set of research material consists of documents relating to these four programs, namely: Project EDUCOM, implemented in 1983, the Programa Nacional de Informática Educativa (PRONINFE), put into operation in 1989, the Programa Nacional de Informática na Educação (PROINFO), in force since 1997, and One Laptop per Child program, implemented since 2010. Guided in the frame of Foucault studies, for analytical exercise, were used governing and governmentality how concepts / tools. The analyzes undertaken about materials research and analytical exercise have identified that spread/dissemination of TD, as well as the promotion of ID on education constitute, in actuality, needs. In this mode, it was perceived that TD dissemination and ID promotion in education can support otherwise conduct guiding, which, together with the production of subjectivities for the constitution of subjects to live according to this way live that are established in Contemporary, produce the electronic governmentality, which consists a form of development of neoliberal governmentality. Thus, it is demonstrated that TD dissemination and ID promotion in education constitute strategies of governmentality electronic operationalized through of strategies smallers, as training of human resources, distribution of computers, production of desire for Internet, education in all areas, networking and availability to access and be accessed. These strategies also operate in the Homo economicus acessibilis constitution, a proper subject for this time where to make use of TD constitutes a necessity. governmentality.
Keywords: Tecnologias digitais; Inclusão digital; Governamentalidade; Digital technologies; Digital inclusion; Governmentality; ACCNPQ::Ciências Humanas::Educação